A highly sensitive gas sensor based on CuO nanoparticles synthetized via a sol–gel method. Issue 83 (22nd August 2016) - Wang, Fang; Li, Hairong; Yuan, Zhaoxin; Sun, Yongzhe; Chang, Fangzhi; Deng, Heng; Xie, Longzhen; Li, Haiyan
Abstract : In this paper, CuO nanoparticles were synthetized via a sol–gel method and their corresponding gas sensor was achieved simultaneously. Abstract : In this paper, CuO nanoparticles were synthetized via a sol–gel method and their corresponding gas sensor was achieved simultaneously. CuO nanoparticle samples were characterized by X-ray diffraction, Raman spectroscopy, X-ray photoelectron spectroscopy and field emission scanning electron microscopy, respectively. The results show that the sample we have synthesized was CuO and the morphology of the sample was nanoparticles with an average diameter of ∼100 nm. We determined the operating temperature of the gas sensors to be 220 °C, considering their appropriate sensitivity, rapid response and the uniformity of testing. Under this working temperature, the sensitivity and response/recovery time of the gas sensor were tested with acetone, methanol and ethanol gas. It was found that the CuO nanoparticles gas sensor performed a high response to the low concentrations of these three gases. At a gas concentration of 0.1 ppm and 10 ppm, the response to the three gases was about 2.5, 1.9, 2.7 and 5.3, 5.9, 5.3, respectively. It is believed that the CuO nanoparticles may be a promising candidate for low concentration reducing volatile organic gases sensing applications.